PENGARUH SATUAN PENGAWASAN INTERN (SPI) TERHADAP UPAYA PENINGKATAN KINERJA PD. PERKEBUNAN PROPINSI SUMATERA UTARA - Muhammad Zilal Hamzah; Musa Ritonga (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
The purpose of this research is to find the influence of internal control unit toward the effort on increasing of finn performance and to know some factors which cause the lack of recommendation. The analisys done by using financial data in the last 5 years (2000-2004) including: productivity report, effectivity report, efficiency report and Return on Investment (R01) report. The results show that production of oil palm tree and natural rubber, effectivity of oil palm tree and natural rubber, efficiency of oil palm tree and ROI have significance influence toward firm performance simultaneously. Otherwise, production of natural rubber gives positive influence but insignificance toward firm performance, if tested partially. Generally, internal control unit has done its job in Perusahaan Daerah (PD) Propinsi Sumatera Utara.Keywords : internal control unit, productivity efficiency, Return on Investment (ROI).